The novel HLA‐B54:01:12 allele, identified by Sanger dideoxy nucleotide sequencing in a Chinese individual - Zhang, Xiao‐qian; An, Lin; Ding, Pei‐pei; Li, Yu‐xia; Li, Li‐min (HLA, 2024)
HLA‐B*54:01:12 differs from HLA‐B*54:01:01:01 by one nucleotide in exon 2.